Investment Under Uncertainty - Lucas, Robert E.; Prescott, Edward C. (Econometrica, 1971)
[This paper determines the time series behavior of investment, output, and prices in a competitive industry with a stochastic demand. It is shown, first, that the equilibrium development for the industry solves a particular dynamic programming problem (maximization of "consumer surplus"). This problem is then studied to determine the characteristics of the equilibrium paths.]